The Interrelationship between Race, Social Norms and Dietary Behaviors among College-Attending Women - Bell, Caryn N. (Am J Health Behav, 2019)
OBJECTIVE: The association between social norms and dietary behaviors is well-documented, but few studies examine the role of race. The aim of this study was to determine the interrelationships between race, social norms, and dietary behaviors. METHODS: Data from the Healthy Friends Network Study (a pilot study of women attending a southern university) was used. Dietary behaviors, social norms and self-identified race were obtained. RESULTS: African Americans had lower odds of daily vegetable (OR=0.55, 95% CI=0.38–0.79) and fruit consumption (OR=0.45, 95% CI=0.30–0.67), but no race difference in frequent consumption of fatty/fried/salty/sugary foods was observed in fully adjusted models. Proximal descriptive norms were associated with all dietary behaviors, but distal injunctive social norms were associated with lower odds of frequent unhealthy food consumption (OR=0.10, 95% CI=0.05–0.21). Race differences in family descriptive norms were found to mediate race differences in vegetable and fruit consumption by 7–9%. However, race differences in friend and family injunctive norms mediated 20–50% of the effects of race on frequent unhealthy food consumption. CONCLUSIONS: Proximal injunctive norms account for race differences in unhealthy food consumption. Future studies should further explicate the mechanisms and seek to utilize social norms in behavior change interventions.